2010
DOI: 10.1007/bf03256358
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Gene Polymorphisms Influence Susceptibility to Cachexia in Patients with Low-Third Gastric Cancer in a Chinese Population

Abstract: Our results indicate that genetic polymorphisms of IL-10 may influence susceptibility to cachexia in patients with low-third gastric cancer in this Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Therefore, our findings strongly suggested that LIF is a cachectic factor in the 85As2-bearing cachexia model. To date, genetic polymorphisms of cytokines such as IL-1␤, IL-8, and IL-10 have been implicated in cachexia pathogenesis in stomach cancer patients (5,26,54). Our study is the first to associate LIF with stomach cancer cachexia.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, our findings strongly suggested that LIF is a cachectic factor in the 85As2-bearing cachexia model. To date, genetic polymorphisms of cytokines such as IL-1␤, IL-8, and IL-10 have been implicated in cachexia pathogenesis in stomach cancer patients (5,26,54). Our study is the first to associate LIF with stomach cancer cachexia.…”
Section: Discussionmentioning
confidence: 61%
“…Since then, researchers have consecutively reported associations of IL-10-819 C/T SNP with the susceptibility to gastric cancer, but with mixed or conflicting results [15-25]. Up to now, there has been only one published meta-analysis article focusing on IL-10-819 C/T SNP [26], but that meta-analysis failed to adopt the most likely appropriate genetic model, and thus the authentic values of statistical results could be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…SNP in the IL-1, IL-6, and IL-10 genes that are linked to production rates of these cytokines have been associated with the prevalence of cachexia in gastric or pancreatic cancer (Tan and Fearon 2010). For example, the 1082G allele in the IL-10 promoter has been validated as a procachectic genotype in an independent cohort (Deans et al 2009;Sun et al 2010a, b). IL-10 has been shown to be elevated in a Myc/mTOR driven murine model of cancer cachexia (Robert et al 2012), as well as in cachectic patients with colorectal cancer (Shibata et al 1996).…”
Section: Discussionmentioning
confidence: 97%
“…By incorporating a definition based on systemic inflammation, we identified a SNP involved in the innate immune response. To date most of the studies on identification of SNPs involved in cancer cachexia has led to the discovery of other SNPs involved in the innate immune system, mainly in the interleukin family of cytokines (Jatoi et al 2007(Jatoi et al , 2010Knoll et al 2008;Zhang et al 2008;Deans et al 2009;Bo et al 2010;Rausch et al 2010;Sun et al 2010a, b) (table 1). SNPs in other biological processes have also been studied for their association with cancer cachexia (Solheim 2011(Solheim , 2012Punzi et al 2012) (table 1).…”
Section: Introductionmentioning
confidence: 97%